2020
DOI: 10.3171/2016.12.jns161713
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of drainage techniques for evacuation of chronic subdural hematoma: a consecutive population-based comparative cohort study

Abstract: OBJECTIVE Surgery for chronic subdural hematoma (CSDH) is one of the most common neurosurgical procedures. The benefit of postoperative passive subdural drainage compared with no drains has been established, but other drainage techniques are common, and their effectiveness compared with passive subdural drains remains unknown. METHODS In Scandinavian population-based cohorts the authors conducted a consecutive, parallel cohort study to compare different drainage techniques. The techniques used were continuous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 26 publications
3
60
0
Order By: Relevance
“…The observational studies that mentioned the Hawthorne effect as an explanation for some of their outcomes were all good quality studies (Table ). Five RCTs were of poor quality, mainly due to personnel not being blinded to the intervention and one was of fair quality as shown in Table .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The observational studies that mentioned the Hawthorne effect as an explanation for some of their outcomes were all good quality studies (Table ). Five RCTs were of poor quality, mainly due to personnel not being blinded to the intervention and one was of fair quality as shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Four trials were based on orthopaedics (three observational studies; one RCT), three on obstetrics (two observational studies; one RCT), three on neurosurgery (two observational studies; one RCT), three on general surgery (one observational study; two RCTs) and one each on cardiothoracic (observational), ear nose and throat (observational) and maxillofacial surgery (RCT). Thirteen studies reported participant gender, being 3178 females (69%) and 1409 males (31%) . The mean age of participants was 61.1 years (Table ) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations